ANALISIS PERKEMBANGAN USAHA INDUSTRI KUE TRADISIONAL BARUASA PADA UD. BARUASA MEMBIRI KENDARI - Riskiya, Arnisa Putri (Universitas Halu Oleo, 2016)
The population in this study were all employees at UD. Baruasa Establishes Kendari, with 22 permanent employees. Sampling using the Total Sampling technique with the population used as samples is 22 and the research informant is the Head of UD. Baruasa Establishes Kendari, Head of Production, Marketing, and Head of Finance at UD. Baruasa Build Kendari.The results showed that the development of industrial businesses carried out at UD. Baruasa Establishing Kendari in general can be said to be good. This can be seen from the profit obtained by UD. Baruasa Establishing Kendari is increasing from year to year in line with the increasing number of customers, as well as an increase in the number of customers along with the increasing marketing area and the increasing taste of the products produced. But in the development of facilities and infrastructure as well as the workforce still need to be developed again given the increasing number of customers and an increasingly broad marketing area.The population in this study were all employees at UD. Baruasa Establishes Kendari, with 22 permanent employees. Sampling using the Total Sampling technique with the population used as samples is 22 and the research informant is the Head of UD. Baruasa Establishes Kendari, Head of Production, Marketing, and Head of Finance at UD. Baruasa Build Kendari.The results showed that the development of industrial businesses carried out at UD. Baruasa Establishing Kendari in general can be said to be good. This can be seen from the profit obtained by UD. Baruasa Establishing Kendari is increasing from year to year in line with the increasing number of customers, as well as an increase in the number of customers along with the increasing marketing area and the increasing taste of the products produced. But in the development of facilities and infrastructure as well as the workforce still need to be developed again given the increasing number of customers and an increasingly broad marketing area.